Identical de novo mutation at the D4F104S1 locus in monozygotic male twins affected by facioscapulohumeral muscular dystrophy (FSHD) with different clinical expression. Issue 9 (September 1998) - Tupler, R; Barbierato, L; Memmi, M; Sewry, C A; De Grandis, D; Maraschio, P; Tiepolo, L; Ferlini, A
Abstract : Facioscapulohumeral muscular dystrophy (FSHD) is a progressive hereditary neuromuscular disorder, transmitted in an autosomal dominant fashion. Its clinical expression is highly variable, ranging from almost asymptomatic subjects to wheelchair dependent patients. The molecular defect has been linked to chromosome 4q35 markers and has been related to deletions of tandemly repeated sequences located in the subtelomeric region detected by probe p13E-11 (D4F104S1). We describe a pair of monozygotic male twins affected by FSHD, carrying an identical de novo p13E-11 EcoRI fragment of paternal origin and showing great variability in the clinical expression of the disease, one being almost asymptomatic and the other severely affected. Their medical history was the same, with the exception of an anti-rabies vaccination performed at the age of 5 in the more severely affected twin. We hypothesise that the vaccination might have triggered an inflammatory immune reaction contributing to the more severe phenotype.